1993
DOI: 10.1037/0022-3514.64.1.141
|View full text |Cite
|
Sign up to set email alerts
|

When ego threats lead to self-regulation failure: Negative consequences of high self-esteem.

Abstract: The tendency for people with high self-esteem to make inflated assessments and predictions about themselves carries the risk of making commitments that exceed capabilities, thus leading to failure. Ss chose their performance contingencies in a framework where larger rewards were linked to a greater risk of failure. In the absence of ego threat, Ss with high self-esteem showed superior self-regulation: They set appropriate goals and performed effectively. Ego threat, however, caused Ss with high self-esteem to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
327
1
13

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 447 publications
(354 citation statements)
references
References 98 publications
(109 reference statements)
13
327
1
13
Order By: Relevance
“…Players from highstatus countries may have an extra intense desire to avoid "losing face" and when this threat is imminent, the result may be high levels of emotional distress. Faced with such uncomfortable states, it has been shown that people tend to search the most immediate escape from the threat (e.g., Baumeister et al, 1993) and in our study we found that players on the high-status teams tended to display shorter response times than players on other teams, possibly indicating a desire to get the situation "over and done with". The same may be the case for teams who have won a major title (i.e., WC/EC) in the past, but then go through many years with no titles, possibly accompanied by accumulated frustration with not living up to this previously demonstrated high standard, which was shown to be related to low response times with a weak trend towards low performance.…”
Section: Discussionsupporting
confidence: 44%
“…Players from highstatus countries may have an extra intense desire to avoid "losing face" and when this threat is imminent, the result may be high levels of emotional distress. Faced with such uncomfortable states, it has been shown that people tend to search the most immediate escape from the threat (e.g., Baumeister et al, 1993) and in our study we found that players on the high-status teams tended to display shorter response times than players on other teams, possibly indicating a desire to get the situation "over and done with". The same may be the case for teams who have won a major title (i.e., WC/EC) in the past, but then go through many years with no titles, possibly accompanied by accumulated frustration with not living up to this previously demonstrated high standard, which was shown to be related to low response times with a weak trend towards low performance.…”
Section: Discussionsupporting
confidence: 44%
“…Do high self-esteem subjects fail to self-regulate and continue to persist at tasks even when such behavior is countexproductive? Baumeister and Heatherton (1991) recently demonstrated the counterproductive influence of high selfesteem in the face of ego-threats on a complex self-regulatory task. Subjects in these experiments choose performance contingencies for themselves on a video game from among several options, such that larger monetary rewards were linked to greater chances of failure.…”
Section: Self-esteem and Self-regulationmentioning
confidence: 99%
“…This process may start when an athlete's self-image is threatened and he/she experiences intense emotional distress. This in turn may cause selfregulation and coping efforts to fail (e.g., Baumeister, Heatherton, & Tice, 1993). In essence, when experiencing intense distress, people seem to think about immediate issues and less on long-term implications from what they are doing.…”
mentioning
confidence: 99%